2022
DOI: 10.3390/pharmacy10050125
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Pharmacy Practice: A Look towards the Future

Abstract: This review looks at the factors that may influence practice in the future. Transformation could occur at 3 levels. Firstly, the traditional profession of the pharmacist as a dispenser of medicines is expanding. Secondly, the pharmacist’s activities are progressing into new healthcare fields. Thirdly, other changes are stimulated by global developments. This review may be helpful for pharmacy and healthcare leaders looking at the future configuration and aims of their pharmacy services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…While it found considerable room for improvement, pharmacy staff were not included in this study, which is symptomatic of the traditional healthcare structures, where pharmacists are strongly associated with more traditional roles such as logistics, procurement and production and less so with medication and patient safety [31]. This is mirrored in many other central European countries who are equally struggling to evolve into more patient facing roles [32,33]. As a result, countries need to invest in stakeholder analysis studies to identify how competency frameworks can be implemented into existing national healthcare structures and education.…”
Section: Discussionmentioning
confidence: 99%
“…While it found considerable room for improvement, pharmacy staff were not included in this study, which is symptomatic of the traditional healthcare structures, where pharmacists are strongly associated with more traditional roles such as logistics, procurement and production and less so with medication and patient safety [31]. This is mirrored in many other central European countries who are equally struggling to evolve into more patient facing roles [32,33]. As a result, countries need to invest in stakeholder analysis studies to identify how competency frameworks can be implemented into existing national healthcare structures and education.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, social safety correlated with the economic effect on action creates the success of the pharmaceutical business, considered as a result of balancing socio-economic objectives [53]. The value bundle thus created gives rise to a high capitalisation of the company [54], reinforcing the economic effect globally [55]. Particularly distinctive effects are obtained in areas touching on specific dimensions of health security [56], i.e., those with a strategic dimension in global health policy [57,58], where the recently explored challenge of finding a vaccine, or a cure for COVID-19, may serve as an example [59].…”
Section: Sustainability In the Pharmaceutical Industrymentioning
confidence: 99%
“…The study found that there are variations within terminology and definitions, frameworks for specialization and advanced practice, professional recognition mechanisms and benefits across countries. Despite the variances, it is clear that professional advancement and the recognition of advancement in practice are developing around the world and this could be due to the increasingly complex nature of pharmaceutical care delivery and a consequent need to be able to endorse professional capabilities [10]. Patient centered pharmacy education initiated in the USA with PharmD model has partially replicated in some other countries, and the largest changes occurred after graduation.…”
Section: Trends In Pharmacy Practice and Education Worldwidementioning
confidence: 99%
“…In contrast, there was a significant variation in the level of implementation of patient-specific clinical pharmacy activities among hospital classes. With activities such as medication counselling, monitoring of adverse drug reactions, and obtaining patient's medication histories provided at a considerably lower level in between 49 and 57% of hospitals [10].…”
Section: Regulationsmentioning
confidence: 99%